KUALITAS MANAJEMEN PENGELOLAAN LIMBAH B3 TERHADAP INDEKS PROPER DI RSUD RAA SOEWONDO PATI - Nia Dhesti Arindita; Mursid Rahardjo; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
RSUD RAA Soewondo Pati is a hospital which has not received assessment ratings for PROPER. Based on the field observations that has done, the management of hazardous and toxic waste in the hospital  has not entirely true and safe according to Health Minister Decision No. 1204 in  2004, Environment Minister Decision No. 03 in 2014, and Government Regulation No. 101 in 2014. This study aims to assess the quality of the management of B3 waste management at RSUD RAA Soewondo Pati  to PROPER index. This research methodology used in this research was qualitative and quantitative approaches with cross sectional design.  The population of this study is was executing management of hazardous and toxic wastes by using total sampling technique. The results showed percentage of obedience data collection type and volume hazardous and toxic waste management, reporting activity, license and validity period, the implementation of permit conditions, the amount of waste managed hazardous and toxic, and B3 waste management with a third-party. Hazardous and toxic waste management in the collection, storage, transportation, and disposal has not managed well according to Health Minister Decision No. 1204 in 2004. Based on the research results of hazardous and toxic waste management derived from 13 primary care hospital with various types of  hazardous and toxic waste generated is plabot, infusion hoses, syringes, tissue and fluids body. The conclusion of the research indicated the assessment results of the management hazardous and toxic waste management by 50% and PROPER ranking was red.